Succession of phytoplankton communities from macro-scale to micro-scale in coastal waters of Qinhuangdao, China - Shang, Xiaomei; Yang, Shuang; Sun, Jun (Frontiers in Marine Science, 2024)
The coastal area of Qinhuangdao, particularly the Changli Gold Coast Nature Reserve, is experiencing ecological degradation and frequent Harmful Algal Blooms (HABs). This study focuses on the changing phytoplankton communities in these coastal waters, examining them from both a macroscopic and microscopic perspective. Utilizing microscopy, molecular techniques, and pigment analysis, seasonal shifts were observed, with diatoms predominating in June and July, and dinoflagellates in August. Our morphological examination enabled the classification of 89 species into four distinct groups. The species Paralia sulcata and Pseudo-nitzschia pungens were most abundant in early summer, while Tripos furca, a dinoflagellate, dominated in August. This indicates a shift in phytoplankton communities due to environmental factors such as phosphate deficiency and high nitrogen/phosphorus ratios. Additionally, the study notes the impact of reduced river runoff and reintroduction of scallop farming contributing to nitrogen-rich eutrophication in August. Molecular analysis revealed a disparity between microscopic observations and the prevalence of Teleaulax blooms during early summer. Elevated concentrations of TN and DOC, coupled with limited water exchange, emerged as primary factors contributing to their occurrence. Sediment analysis revealed a high diversity but low abundance of dinoflagellates in August, with a significant presence of harmful species. The study highlights the shift from diatoms to harmful dinoflagellate populations, exacerbated by eutrophication and pollution, leading to HABs. These findings provide a theoretical basis for understanding toxic algal blooms and are crucial for environmental agencies in developing strategies to protect and sustainably develop offshore environments.